The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/idd-09-2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of personality traits on information needs and seeking behavior of LIS students in Pakistan

Abstract: Purpose This paper aims to identify the personality traits (agreeableness, openness to experience, extraversion, conscientiousness and neuroticism) of library and information science (LIS) students in Pakistan. The difference among the personality traits of LIS students toward their information needs and seeking behavior is also analyzed. Design/methodology/approach Two instruments, namely, BFI scale and a self-structured instrument were used to collect the data. Kruskal–Wallis test was applied to find out d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…However, that correlation was indirect in the sense that being open meant that students were more likely to be deep learners and have higher self-efficacy related to using computers, therefore they had higher information literacy levels. Ahmed et al (2019) found that extraverts were more concerned about information. Halder et al (2010) found that "Information seeking behaviour as a whole was positively correlated with extraversion, openness and conscientiousness and negatively correlated with neuroticism.…”
Section: Figure 5 Summary Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, that correlation was indirect in the sense that being open meant that students were more likely to be deep learners and have higher self-efficacy related to using computers, therefore they had higher information literacy levels. Ahmed et al (2019) found that extraverts were more concerned about information. Halder et al (2010) found that "Information seeking behaviour as a whole was positively correlated with extraversion, openness and conscientiousness and negatively correlated with neuroticism.…”
Section: Figure 5 Summary Of Resultsmentioning
confidence: 99%
“…The opposite of A would include such traits as indifference, self-centeredness, and jealousy (Howard & Howard, 1995), critical and impatient (Kwon and Song, 2011). Those with this trait tend to use a variety of information-searching techniques (Ahmed et al, 2019) and may be motivated to search for information (Costa & McCrae, 1992). Schmidt and Wolff (2016) found that Agreeableness was positively correlated with use of different search strategies.…”
Section: Personality and Isbmentioning
confidence: 99%
See 2 more Smart Citations
“…Chakraborty 2010;O'Brien, Dickinson, and Askin 2017;Harati et al 2019;Ahmed, Rehman, and Sheikh 2019;Thindwa, Chawinga, and Dube 2019) shows the importance of this variable in using library resources and services. Therefore, the necessity of assessing the influence of individuals' features on developing the library clients' impulsive behaviours is justifiable…”
mentioning
confidence: 99%